Негативната теологија во гностичките извори - Тодоровска, Марија (ЗКФМ Антика, 2018)
The article briefly lists the formulations in the Gnostic sources which might be regarded as negative theology. Therefore, the question about the formulae of negative theology is raised ‒ the various apophatic approaches to the ineffable and the unknowable (god, the first principle, the highest reality) ‒ through abstaining from speech and naming, privative attributes, and the denial of certain characteristics of divinity. Several Gnostic texts that contain either obvious negative‐theological stances, or seemingly kataphatic formulations, which serve, however, to convey their own inadequacy when talking about the excellence of god are shown. The ways in which the speech about the defining, naming and knowing of god is formulated in the Gospel of Truth and The Tripartite Tractate are shown; as well as some aspects of the cosmological and ontological systems from the Valentinian school (Valentinus, Ptolemy, Marc/osian), which contain significant elements from the sphere of negative theology; the concept of god that is not ineffable, but so beyond the possibilities of knowledge and naming, that is not‐even-ineffable in Basilides; the apophatic formulations in the poetic language in the Apocryphon of John, and those in the Letter of Eugnostos; and the relevant parts from the complex ontological‐theological system exposed through revelations to Allogenes (Allogenes XI, 3)
Negative Theology in the Gnostic Sources
Keywords: Gnostics, negative theology, Basilides, Allogenes